IMT-07 CLINICAL TRIAL OF A COCKTAIL WILMS' TUMOR 1 (WT1) VACCINATION USING TWO HLA CLASS I PEPTIDES AND ONE CLASS II PEPTIDE FOR RECURRENT MALIGNANT GLIOMAS. (16th December 2019) - Kagawa, Naoki; Oji, Yusuke; Tsuboi, Akihiro; Hirayama, Ryuichi; Kijima, Noriyuki; Kinoshita, Manabu; Oka, Yoshihiro; Sugiyama, Haruo; Kishima, Haruhiko
Abstract: PURPOSE: Our clinical trials shows the safety and clinical efficacy of Wilms' tumor 1 (WT1) human leukocyte antigen (HLA) class I (Izumoto S et al. J Neurosurg. 2008) and class II (Tsuboi A et al. Cancer Immunol Immunother. 2019) peptide vaccination for recurrent malignant gliomas have been established. We have developed a cocktail vaccine (WT1 trio) containing two class I peptides (HLA-A*24:02 and HLA-A*02:01) and one II class peptide to improve more effective immunological response and improve patient's prognosis. Clinical trial of a cocktail vaccination using WT1 HLA class I and II peptides for recurrent malignant gliomas is planned to verify its safety, clinical efficacy and usefulness of surrogate markers. PATIENTS AND METHODS: Twenty-three patients with recurrent malignant gliomas, which showed WT1-positive in tumor samples and HLA-A*24:02 or HLA-A*02:01-positive in blood sample, were enrolled. These patients (age: 26–72 years old, average: 49.4) included 15 cases of glioblastomas and 8 of anaplastic astrocytomas. Patients received a WT1 trio vaccine intradermally, 7 times at 2-week intervals during 3 months.WT1-DTH and WT1-IgG antibody were regularly measured. Vaccine-related adverse events, best clinical response and the transfer rate of long-term administration of WT1 trio vaccination were estimated. RESULTS: WT1-DTH positive cases were 12, WT1-IgG antibody positive were in 11. In most patients, WT1 -DTH positiveness coincided with that of WT1-IgG antibody. 9 of 11 cases showed stable disease at 3 months and transferred long-term administration of WT1 trio vaccination. Transfer rate in GBM and AA of long-term administration was 33% and 25%, respectively. Grade1 skin eruption was observed at the injection sites in 15 cases, but no significant adverse events related with vaccination were shown. CONCLUSION: the safety and clinical efficacy of WT1 trio vaccination was verified for recurrent malignant gliomas. WT1-DTH and WT1-IgG antibody may be useful surrogate markers.